Wood Pellet Driven-Biochar Characterization Produced at Different Targeted Pyrolysis Temperatures - Donghyuk Chun; Irma Thya Rani; Jiho Yoo; Byung Bae Park; Wahyu Hidayat; Bangun Adi Wijaya; Sihyun Lee; Sangdo Kim; Hokyung Choi; Hyuk Im; Soohyun Kim (Jurnal Sylva Lestari, 2023)
The imperative transition to renewable energy drives the need for innovation. Biomass, particularly wood pellets, has demonstrated poor performance in co-firing scenarios. This study employed pyrolysis to convert wood pellets into biochar with improved fuel quality. The biochar production and characterization were investigated at pyrolysis temperatures of 400°C to 500°C. The findings revealed significant improvements: the observed fixed carbon content increased from 67.2% to 78.8%, and the calorific value increased 1.2 times higher within the pyrolysis temperature increased. On the other hand, as the pyrolysis temperature increased from 400°C to 500°C, biochar yields decreased from 49% to 37%. Thermogravimetric (TG) analysis revealed distinct weight loss during heating, illuminating component volatilization and residue accumulation. Furthermore, Fourier transform infrared (FTIR) spectroscopy elucidated structural changes, demonstrating the evolution of cellulose and hemicellulose into aromatic structures. Ultimately, these insights into biochar characteristics informed the optimization of pyrolysis processes, contributing to the production of superior biochar for renewable energy applications. Keywords: biochar, biomass, carbon storage, pyrolysis, wood pellet